Atopic eczema patients and healthcare professionals join forces in Malta - Jean‐François Stalder; Hélène Aubert; Sebastien Barbarot; Jean‐Marc Chavigny; Mette Deleuran; Lawrence F. Eichenfield; May El Hachem; Peter Lio; Danielle Marcoux; Christine Roxburgh; Markéta Saint Aroman; Fanny Sentenac; et al. (Wiley, 2023)
Abstract Atopic patients, multi‐disciplinary specialists, caregivers, and experts from all over the world participated in the International Meeting of the Eczema Foundation in Malta (IMEF). During this 4‐day conference, attendants addressed the challenges pertaining to the management of atopic dermatitis by sharing their experience in the form of presentations, discussion sessions, workshops, and a plenary session. This article aims to report on what we consider to be a successful attempt to unite patients and caregivers in the quest for improved treatment of atopic dermatitis through the implementation of therapeutic patient education.